The Impact and Causes of Subsidence in the Exmouth Sub-basin, Northern Carnarvon Basin. Issue 1 (1st December 2019) - Makuluni, Patrick; Clark, Stuart; Hauser, Juerg
Summary: Understanding the kinematic processes around the formation of sedimentary basins is central to quantifying their resource potential. Building accurate kinematic models is a subjective and time-consuming process which requires incorporation of both vertical and lateral motions within sedimentary basins. Majority of plate reconstruction studies mostly focus on lateral plate motions hence, methods of subsidence analysis have seen slow evolution. So far subsidence analysis has been performed in one dimension only using borehole data and the results are interpolated or extrapolated over an area to give subsidence map of a region. This approach is prone to errors as it may not incorporate the effects of differential compaction within basins with complicated geology. We propose the introduction of an algorithm that performs decompaction and backstripping on 2D seismic cross-sections to improve the accuracy of subsidence analysis in the sedimentary basins. The decompaction component of the algorithm is based on the bisection method of a Python programming language. We applied the algorithm on an 87km wide seismic cross-section from the Exmouth Sub-basin of the Northern Carnarvon Basin in the Australian North West Shelf. The algorithm highlighted effects of differential compaction and quantified the spatial and temporal variability of subsidence within the area. One unique feature in the results is the variation of the basement morphology with time. This may be caused by faulting of the basement rocks from tectonic events and may also be due to the differential deflection of the basement from sediment loading. The tectonic subsidence periods coincide with the major tectonic events within the region as proposed by literature